IFN‐α promotes rapid human Treg contraction and late Th1‐like Treg decrease. Issue 3 (26th February 2016) - Pacella, Ilenia; Timperi, Eleonora; Accapezzato, Daniele; Martire, Carmela; Labbadia, Giancarlo; Cavallari, Eugenio N.; D'Ettorre, Gabriella; Calvo, Ludovica; Rizzo, Fabiana; Severa, Martina; Coccia, Eliana M.; Vullo, Vincenzo; et al.
Abstract : IFN‐α restrains Tregs in vitro and in vivo via induced apoptosis, a decrease in Th1‐like Tregs, inhibiting IL‐12‐driven polarization, and depleting IL‐12 sources. Abstract : Type I IFNs are pleiotropic cytokines that exert concerted activities in the development of antiviral responses. Regulatory T cells represent a physiologic checkpoint in the balance between immunity and tolerance, requiring fine and rapid controls. Here, we show that human regulatory T cells are particularly sensitive to the sequential effects of IFN‐α. First, IFN‐α exerts a rapid, antiproliferative and proapoptotic effect in vitro and in vivo, as early as after 2 d of pegylated IFN/ribavirin therapy in patients with chronic hepatitis C. Such activities result in the decline, at d 2, in circulating regulatory T cell frequency and specifically of the activated regulatory T cell subset. Later, IFN‐based therapy restrains the fraction of regulatory T cells that can be polarized into IFN‐γ‐producing Th1‐like regulatory T cells known to contribute to chronic immune activation in type 1 inflammation. Indeed, Th1‐like regulatory T cell frequency significantly declines after 30 d of therapy in vivo in relation to the persistent decline of relevant IL‐12 sources, namely, myeloid and 6‐sulfo LacNAc‐expressing dendritic cells. This event is recapitulated by experiments in vitro, providing evidence that it may be attributable to the inhibitory effect of IFN‐α on IL‐12‐induced, Th1‐like regulatory T cell polarization. In summary, our results suggest that IFN‐α‐driven, early regulatory T cell depletion contributes to the development of antiviral immunity, ultimately resulting in the resolution of type 1 inflammation.